Controversies on the Philosophy of Social and Humanistic Sciences: Historical Synthesis - Chávez Rodríguez, Justo Alberto (Atenas, 2017)
Philosophical reflection on the social and humanistic sciences and their historical location is necessary for scientific studies within the object of these disciplines. The analysis and the necessary contextualization of each work or representative figure of the prevailing positions at each stage as an expression of the controversy over the scientific statute of the social and human sciences is the result achieved by the purpose of these reflections.